Assessing the Differential Impact of Vacancy on Criminal Violence in the City of St. Louis, MO. (June 2021) - Fox, Branson; Trolard, Anne; Simmons, Mason; Meyers, Jessica E.; Vogel, Matt
This study employs risk terrain modeling to identify the spatial correlates of aggravated assault and homicide in St. Louis, MO. We build upon the empirical literature by (1) replicating recent research examining the role of vacancy in the concentration of criminal violence and (2) examining whether the environmental correlates of violence vary between north and south St. Louis, a boundary that has long divided the city along racial and socioeconomic lines. Our results indicate that vacancy presents a strong, consistent risk for both homicide and aggravated assault and that this pattern emerges most clearly in the northern part of the city which is majority African American and has suffered chronic disinvestment. The concentration of criminal violence in South City is driven primarily by public hubs including housing, transportation, and schools. Our results underscore the importance of vacancy as a driver of the spatial concentration of violent crime and point to potential heterogeneity in risk terrain modeling results when applied to large metropolitan areas. Situational crime prevention strategies would be well served to consider such spatial contingencies as the risk factors driving violent crime are neither uniformly distributed across space nor uniform in their impact on criminal violence.